1995
DOI: 10.1093/rheumatology/35.11.1178
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor v Gene Mutation Increases the Risk of Venous Thrombosis in Behçet's Disease

Abstract: We investigated the prevalence of the coagulation factor V gene G1691A mutation in 64 patients with Behçet's disease (BD) and in 107 apparently healthy individuals. The mutation was present in the heterozygous state in 37.5% of the patients with a history of deep vein thrombosis (12/32) and in 9.4% of the patients without any thrombotic event (3/32). Eleven healthy individuals were also heterozygous for the mutation (10.3%). The prevalence of the mutation in BD patients with and without thrombosis was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(35 citation statements)
references
References 9 publications
(11 reference statements)
2
32
1
Order By: Relevance
“…The prevalence of the FV 1691A mutation in BD varies from 0 to 38% [16][17][18][19][20][21][22][23]. In our study the frequency of heterozygous carriers of the FV 1691A mutation was 16.9% in all BD patients, 25.9% in BD patients with venous thrombosis, and 8.8% in healthy subjects.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The prevalence of the FV 1691A mutation in BD varies from 0 to 38% [16][17][18][19][20][21][22][23]. In our study the frequency of heterozygous carriers of the FV 1691A mutation was 16.9% in all BD patients, 25.9% in BD patients with venous thrombosis, and 8.8% in healthy subjects.…”
Section: Discussionmentioning
confidence: 47%
“…Recently, it has been suggested that procoagulant mutations may play a role in the development of thrombotic events in BD patients. Several groups have studied the contribution of FV 1691A (Leiden) and PT 20210A mutations to thrombotic tendency in BD patients [16][17][18][19][20][21][22][23]. However, there are some controversies in this issue mainly resulting from features of the study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the defects in fibrinolytic system have been examined, but they have not had any relation with thrombosis formation in BD (9,10). In a study, Gül et al suggested that G1691A mutation in factor V can be related to the thrombosis formation of deep veins in BD (11). But, based on the recent evidence, the thrombosis formation in BD has not been confirmed yet (8).…”
Section: Discussionmentioning
confidence: 99%
“…In the light of all these studies, it is now thought that in BD venous thrombosis develops as a result of an inflammation on the vein wall. There is a vessel wall damage and nonspecific inflammation especially in the vein adventitia [13].…”
Section: Introductionmentioning
confidence: 99%